MEMBER SATISFACTION AND LOYALTY MODEL IN COOPERATIVES: THE ROLE OF CUSTOMER RELATIONSHIP MARKETING, REFERENCE GROUPS, AND SERVICE QUALITY - Junaidi Junaidi; Jennifer Chandra; Layla Hafni; Martha Ng (Institut Bisnis dan Teknologi Pelita Indonesia, 2026)
The purpose of this study is to analyze the influence of customer marketing relationships, reference groups, and service quality on the satisfaction and loyalty of members of the Rimba Mutiara Banso Cooperative in Koto Gasib District, Siak Regency. This research employs a quantitative approach. The subjects of the study were all division heads who are members of the Rimba Mutiara Banso Cooperative, totaling 61 individuals. Data were collected using a questionnaire measured with a Likert scale. The data analysis technique used in this study is the statistical method of Structural Equation Modeling (SEM), specifically Partial Least Squares Structural Equation Modeling (SEM-PLS). The findings show that: customer marketing relationship has a significant effect on member satisfaction; reference groups have a significant effect on member satisfaction; service quality has a significant effect on member satisfaction; customer marketing relationship has a significant effect on member loyalty; reference groups do not have a significant effect on member loyalty; service quality does not have a significant effect on member loyalty; and member satisfaction has a significant effect on member loyalty. Tujuan penelitian ini adalah untuk menganalisis pengaruh hubungan pemasaran pelanggan, kelompok referensi, dan kualitas layanan terhadap kepuasan dan loyalitas anggota Koperasi Rimba Mutiara Banso di Kecamatan Koto Gasib, Kabupaten Siak. Penelitian ini menggunakan pendekatan kuantitatif. Subjek penelitian adalah semua kepala divisi yang merupakan anggota Koperasi Rimba Mutiara Banso, dengan total 61 orang. Data dikumpulkan menggunakan kuesioner yang diukur dengan skala Likert. Teknik analisis data yang digunakan dalam penelitian ini adalah metode statistik Structural Equation Modeling (SEM), khususnya Partial Least Squares Structural Equation Modeling (SEM-PLS). Hasil penelitian menunjukkan bahwa: hubungan pemasaran pelanggan memiliki pengaruh signifikan terhadap kepuasan anggota; kelompok referensi memiliki pengaruh signifikan terhadap kepuasan anggota; kualitas layanan memiliki pengaruh signifikan terhadap kepuasan anggota; hubungan pemasaran pelanggan memiliki pengaruh signifikan terhadap loyalitas anggota; kelompok referensi tidak memiliki pengaruh signifikan terhadap loyalitas anggota; kualitas layanan tidak memiliki pengaruh signifikan terhadap loyalitas anggota; dan kepuasan anggota memiliki pengaruh signifikan terhadap loyalitas anggota.